2017
DOI: 10.1007/s13300-017-0237-8
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Receptor Agonist Treatment Attributes Important to Injection-Experienced Patients with Type 2 Diabetes Mellitus: A Preference Study in Germany and the United Kingdom

Abstract: IntroductionThis study assessed the relative importance of treatment-related attributes in influencing patient preferences for glucagon-like peptide-1 receptor agonists (GLP-1RAs) among injection-experienced type 2 diabetes mellitus (T2DM) patients in Germany and the United Kingdom.MethodsT2DM patients experienced with injecting once-weekly (QW) exenatide or once-daily (QD) liraglutide completed an online discrete-choice experiment (DCE) survey. Patients chose between hypothetical blinded treatment profiles re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 55 publications
(78 reference statements)
0
43
0
Order By: Relevance
“…Of the ten records included, eight studies had compared patient preferences between different GLP1 RA-attribute profiles,12,15,1823 one had compared a GLP1 RA versus insulin-glargine profile,17 and one compared patient preference among GLP1 RA profiles and between a GLP1 RA versus insulin-glargine profile 24. Results for GLP1 RA versus GLP1 RA-attribute comparisons and GLP1 RA versus insulin glargine-attribute comparisons are summarized separately.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the ten records included, eight studies had compared patient preferences between different GLP1 RA-attribute profiles,12,15,1823 one had compared a GLP1 RA versus insulin-glargine profile,17 and one compared patient preference among GLP1 RA profiles and between a GLP1 RA versus insulin-glargine profile 24. Results for GLP1 RA versus GLP1 RA-attribute comparisons and GLP1 RA versus insulin glargine-attribute comparisons are summarized separately.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were multinational. DCEs were employed for preference elicitation in six studies,15,1720,23 two studies used TTO,12,21 one reported a DCE with WTP,24 and one study used both TTO and DCE 22. Sample sizes ranged from 182 to 1,482 participants, and all studies included adults with T2DM.…”
Section: Resultsmentioning
confidence: 99%
“…People with type 2 diabetes typically report a preference for oral medications over injections, and, where injectable medications are required, a preference for non‐insulin injectables and regimens which require fewer injections . Nonetheless, delayed uptake and problematic medication‐taking behaviours are observed across diabetes medicines administered both orally and via injection.…”
Section: What Have the Past 25 Years Of Research Told Us?mentioning
confidence: 99%
“…The 18 applied DCEs addressing understanding in the pretesting phase all used the concept of understanding as a way to modify or revise the DCE instrument before final roll out [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Most used pretesting to test or confirm understanding in relation to the terminology of attributes and medical concepts.…”
Section: Applied Dces Addressing Understanding In the Pretesting Phasementioning
confidence: 99%